Incidence of oncogenic HPV and HPV-related dysplasia five years after a negative HPV test by self-sampling in elderly women - Ruth S. Hermansson; Matts Olovsson; Inger Gustavsson; Ulf Gyllensten; Olga Lindkvist; Julia Hedlund Lindberg; Gabriella Lillsunde-Larsson; Annika K. Lindström (Infectious Agents and Cancer, 2022)
Abstract Purpose Cervical cancer prevention for older women can be challenging since there are no specific guidelines for this group. This study aimed to determine the incidence of oncogenic HPV and HPV-related dysplasia in elderly women 5 years after being HPV negative. Methods Invited women participated five years earlier in a study where self-sampling for HPV testing was applied, at this time, they were all HPV negative. The women were now, five years later invited to perform self-sampling for HPV testing. Women with a positive result performed a repeat HPV test. Those with a positive repeat HPV test were examined by colposcopy, biopsy and cytology. Results Of the 804 invited women, 634 (76.9%) agreed to participate in the study and a self-sampling kit was sent to them. Of these, 99.6% (632/634) sent a sample to the HPV laboratory. The participation rate in each age group was 93.3% at age 65, 74.0% at age 70, 80.7% at age 75 and 64.6% at age 80. Overall 18 women (2.8%, 95% CI 3.2 to 6.0) were HPV positive in the first test and 8 (1.3%, 95% CI 0.6 to 2.6) in the second test. Sampling for the second test was done on average 5.4 months after the first test. Fifty per cent (4/8) of the women with a positive repeat test had dysplasia in histology. Conclusion The incidence of HPV in previously HPV-negative elderly women was low. Among women who were HPV positive in a repeat test, there was a high prevalence of low grade dysplasia.